2018
DOI: 10.5897/jssem2018.0684
|View full text |Cite
|
Sign up to set email alerts
|

Farmers perception of soil and watershed degradation and the assessment of soil nutrients status under agroforestry systems in the Western Highlands of Cameroon: Case of Ako sub division

Abstract: The objective of this study was to assess farmers' perception regarding the activities which degrade the soil and watershed and to analyze soil nutrients status under different agroforestry systems. The aim of the study was to identify and promote locally-known agroforestry-based practices for soil and watershed conservation in the savannah highland area of Cameroon. Semi-structured questionnaires were administered to 120 farmers purposively selected from 10 villages in the Ako sub division characterized by fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…Since the slash and burn practice and the improved fallow were not prominent, the two main agroforestry practices identified in this area were life fences (AFP1) and scattered trees on farm lands (AFP2). This finding is different from the findings of Munjeb (2018), and Awazi et al (2019) who found a multitude of agroforestry practices on farmlands in north western Cameroon. Other studies undertaken by Nair (1989) and Nair (1993) found a multitude of agroforestry practices implemented by farmers across the tropics.…”
Section: Comparison Between the Two Major Agroforestry Practices Idencontrasting
confidence: 98%
See 1 more Smart Citation
“…Since the slash and burn practice and the improved fallow were not prominent, the two main agroforestry practices identified in this area were life fences (AFP1) and scattered trees on farm lands (AFP2). This finding is different from the findings of Munjeb (2018), and Awazi et al (2019) who found a multitude of agroforestry practices on farmlands in north western Cameroon. Other studies undertaken by Nair (1989) and Nair (1993) found a multitude of agroforestry practices implemented by farmers across the tropics.…”
Section: Comparison Between the Two Major Agroforestry Practices Idencontrasting
confidence: 98%
“…This is the first study in Cameroon to produce such unprecedented findings, showing that scattered trees on croplands play a major role in improving soil fertility in south western Cameroon. Nevertheless, other studies have equally shown that agroforestry practices in general have the capacity to improve soil fertility (Young, 1997;Asaah et al, 2011;Leakey, 2017;Awazi & Tchamba, 2018;Munjeb, 2018).…”
Section: Comparison Between the Two Major Agroforestry Practices Idenmentioning
confidence: 99%